2020
DOI: 10.1002/agg2.20028
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biochar application on quality of flooded sandy soils and corn growth under greenhouse conditions

Abstract: Seasonal flooding following heavy rain deposits large amounts of sediments on productive lands in the lower parts of fields in western Tennessee. The deposited sediments have high proportion of sand particles that negatively affect soil physiochemical properties, which make the soil uneconomic for farming. Soil amendments such as biochar, a by‐product of renewable energy production from organic waste materials, have the potential to remediate sandy soil left after flood events and improve crop yields by increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The potential to significantly increase soil WHC (Atkinson et al, 2010;Basso et al, 2013;Blanco-Canqui, 2017;Katterer et al, 2019;Jahromi et al, 2020;Paetsch, et al, 2018) of coarse-textured soils in a water-stressed region was the main goal for adding biochar in our studied soil. However, another attractive characteristic of amending soils with biochar is that it could function as alternative source of nutrients that support biomass production (Gaskin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The potential to significantly increase soil WHC (Atkinson et al, 2010;Basso et al, 2013;Blanco-Canqui, 2017;Katterer et al, 2019;Jahromi et al, 2020;Paetsch, et al, 2018) of coarse-textured soils in a water-stressed region was the main goal for adding biochar in our studied soil. However, another attractive characteristic of amending soils with biochar is that it could function as alternative source of nutrients that support biomass production (Gaskin et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Our results are somewhat in agreement with other studies that evaluated different rates of biochar application under field and controlled conditions and found that only the highest rates significantly increased the amount of water stored in the soil. For instance, Jahromi et al (2020) found that the highest rates (20%, v/v) of two types (mixed hardwood with and without bark) of biochar increased WHC of sandy soils by 62% compared with the untreated control. Similarly, Obia et al (2016) reported that a single application of maize (Zea mays L.) cob and rice (Oryza sativa L.) husk biochars (either 17.5 or 35 Mg ha -1 ) with particle sizes ≤0.5 and 1-5 mm and 0.3 g cm -3 density to sandy loam and loamy sand soils increased WHC by 8% and soil aggregate stability by 13% after one growing season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aeolian sandy soil is one of the most important reserved, cultivated land resources in arid and semi-arid areas. But due to its disadvantages of having low nutrient content and poor water retention, crops planted in it face adverse environmental effects ( Baiamonte et al., 2020 ; Jahromi et al., 2020 ; Ibrahim et al., 2021 ), which leads to poor crop growth and low yield. Maize ( Zea mays L.), one of the world’s most important food crops, is mainly planted in semi-arid areas ( Ul-Allah et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%